gga-miR-148a-5p-Targeting PDPK1 Inhibits Proliferation and Cell Cycle Progression of Avain Leukosis Virus Subgroup J (ALV-J)-Infected Cells - Yu, Heling; Xu, Hengyong; Yan, Chaoyang; Zhu, Shiliang; Lan, Xi; Lu, Yuxiang; He, Qijian; Yin, Huadong; Zhu, Qing; Zhao, Xiaoling; Li, Diyan; Liu, Yiping; et al. (Frontiers in Cell and Developmental Biology, 2020)
Avian leukosis virus subgroup J disease (ALV-J) is a contagious and immunosuppressive avian disease caused by ALV-J virus. Although miRNA participate in various biological processes of tumors, little is known about the potential role of miRNA in ALV-J. Our previous miRNA and RNA sequencing data showed that the expression of gga-miR-148a-5p was significantly different in ALV-J infected chicken spleens compared with non-infected chickens. The aim of this study was to investigate the functional roles of gga-miR-148a-5p and identify downstream targets regulated by gga-miR-148a-5p in ALV-J infection chicken. We found that the expression of gga-miR-148a-5p was significantly down-regulated during ALV-J infection of chicken embryo fibroblasts (CEF). Dual luciferase reporter assays demonstrated that PDPK1 is a direct target gene of gga-miR-148a-5p. In vitro, overexpression of gga-miR-148a-5p significantly promoted ALV-J infected CEF cell proliferation, included cell cycle, whereas inhibition of gga-miR-148a-5p had an opposite effect. Inhibition of PDPK1 promoted the proliferation of ALV-J infected cells but had no effect on the activity of NF-κB. Together, these results suggested that gga-miR-148a-5p targets PDPK1 to inhibit the proliferation and cell cycle of ALV-J infected CEF cells. Our study provides a new understanding for the tumor mechanism of ALV-J infection.